Systèmes de cybersécurité et de défense : une étude de cas sur la Chine - Mohammed BOUMERZAK, Ikram BOUMERZAK & Abdelhadi DERRAR, (Akofena)
Abstract: In the realm of national security, cybersecurity planning within a complex system directly contributes to achieving cyber resilience. For a nation like China, whose operational integrity and strategic objectives are increasingly dependent on its digital systems, the core purpose of its cyber defense framework is to ensure the smooth execution of national missions against both internal and external cyber threats. Establishing effective cyber resistance requires substantial allocation of organizational, human, material and financial resources to implement proactive measures, activities and procedures, thereby minimizing residual security risk. This remaining risk which cannot be entirely eliminated must be acknowledged and managed within the national security framework. This paper investigates how China is navigating the rising tide of global security risks to enhance its cyber resistance. Our research aims to provide insights into China's approach to integrating cyber and information security recognizing that the methods for identifying and mitigating novel threats remain a continuous challenge. To effectively counter these evolving dangers there is a critical need to cultivate "knowledge about ignorance" and to continually develop cyber capabilities grounded in sound cybersecurity and defense principles.